The clinical significance of 15q11.2 BP1-BP2 duplications: - Where do we stand? - Serafim, Silvia (2016)
The 15q11.2-q13 region has been well characterized, being associated with a range of syndromatic copy number variants (CNVs), and comprises five established break points sites (BP1 to BP5). While the clinical effect for BP1-BP3, BP2-BP3 and BP4-BP5 CNVs is well established, the same cannot be said for BP1-BP2 CNVs. Recently the 15q11.2 BP1-BP2 deletion has been reviewed, emerging as a microdeletion syndrome with low penetrance and variable expressivity being the CNV frequently inherited from a healthy parent. This microdeletion is considered to be a risk factor for several neurodevelopment disorders. For the reciprocal duplication the picture has been less conclusive. Aiming for a better understanding of the clinical significance of this CNV, we collected patients with intellectual disability and/or other clinical features, referred for microarray testing, gathering clinical details for the ones with the duplication. Data was collected from two genetic laboratories. With a total of 1545 patients, we identified eleven carrying the duplication at 15q11.2 BP1-BP2. It was possible to assess inheritance in only four cases, all inherited from a healthy parent. All patients presented intellectual disability,and facial dysmorphism was the second most common feature observed. Microcephaly, autism, congenital abnormalities, dystonia and cataplexy where reported individually. The magnitude of the effect of 15q11.2 duplication remains elusive, and the outcome unclear, posing a major challenge to genetic counseling. Nevertheless, we expect the collection of more of these cases will establish this gain, as it happened with the reciprocal deletion, as a microduplication syndrome with low penetrance and variable expressivity.